CORRUPTION CONTROL AS A CATALYST FOR ECONOMIC GROWTH: EVIDENCE FROM AFRICA'S LEAST CORRUPT COUNTRIES - Phillips, Phillips P. C; Hansen , B. E (Journal of Healthcare Management and Administration (JHMA), 2022)
Corruption is a pervasive obstacle to economic development worldwide, affecting both developed and developing countries. This study focuses on the impact of corruption control on the economic growth of ten African countries identified as the least corrupt in the continent. By examining the positive effects of corruption control in these countries, the study aims to contribute to the existing body of knowledge and provide insights for policymakers seeking efficient strategies to strengthen anti-corruption agencies. The research adopts an econometric approach to investigate the extent to which corruption control influences economic growth. Previous studies have primarily focused on the relationship between corruption and economic growth, while this study specifically examines the role of corruption control. The findings of this study can offer alternative options for countries struggling with corruption tendencies, enabling them to enhance their policies and promote economic and social development. Moreover, the study's recommendations and policies can be applied to other African countries facing similar challenges. The paper is divided into five sections, beginning with an introduction followed by a review of literature, methodology, data sources, and the empirical model. The results are discussed in section IV, and the study concludes with policy implications in section V.